Studies on the isolation and identification of the antibacterial compound from Prunella vulgaris L. Flower extract - Khursheed Ahmad Dar; S. Senthilmurugan; Sajad Ali; Mohammad Khalid Al-Sadoon; Bilal Ahamad Paray (Journal of King Saud University: Science, 2022)
Prunella vulgaris is an important medicinal plant with a wide range of pharmacological properties. The present research is aimed to investigate the functional groups, phytochemical constituents, in-vitro antibacterial activity and isolation of antibacterial compound from flower extract of P. vulgaris. Here, we examined the antibacterial activity of P. vulgaris extract against gram positive (Streptococcus pneumonia, Enterococcus faecalis and Staphylococcus aureus) and gram negative (Escherichia coli and Klebsiella pneumonia) bacterial strains. Based on our results, the extract showed strong antibacterial activity against all of the pathogens used in this study. The minimum inhibitory concentration (MIC) of P. vulgaris extract was determined by broth micro dilution method. Further, the extract was subjected to column chromatography to get the active fractions. To identify and isolate the antibacterial molecule, the active fraction (fraction-6) was subjected to spectral analysis using the Fourier-transform infrared spectroscopy (FT-IR), 1H 13C nuclear magnetic resonance (NMR), and mass spectroscopy (MS). On the basis of functional group analysis, molecular formula and molecular mass, the isolated compound was identified as [(2-(E)-3-(3-4-dihydroxyphenyl) acryloyloxy)-3-(3, dihydroxyphenyl) propanoic acid (Rosmarinic acid)] from the active fraction of P. vulgaris flower extract. In conclusion P. vulgaris has enormous therapeutic and pharmacological significance and can be used in the research and development of antibacterial medications as well as other pharmacological endeavors.